UANG PANAI DAN TRADISI PERNIKAHAN BUGIS: PERSPEKTIF ISLAM DALAM LITERATUR - Herianti Herianti; Basri Basri; Jumarni Jumarni; Novita Sari (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2026)
Abstract: Bugis wedding traditions and the uang panai (customary bride price) reflect cultural, social, and religious values. However, uang panai is often perceived as a determining factor in marriage decisions, creating various perspectives within society. In Islam, mahar is an essential element of marriage, while uang panai is not specifically regulated. This study aims to examine Bugis wedding traditions and uang panai from an Islamic perspective using a literature review method. The findings show that Bugis wedding rituals contain Islamic values, whereas uang panai is a cultural practice rather than a religious obligation. This study contributes to a broader understanding of Indonesia’s cultural diversity, particularly Bugis customs.